TINJAUAN HUKUM INTERNASIONAL MENGENAI OTORISASI PENGGUNAAN PRIVATE MILITARY CONTRACTORS (PMC) OLEH DEWAN KEAMANAN PBB - Elsyam Maulana; Suhaidi Suhaidi; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2017)
ABSTRACT Elsyam Maulana Suhaidi Sutiarnoto In the political history of mankind, most of many events which were written are wars and peace. From the World War I, World War II, The Cold War, and apparently most of recent wars occurred, need an abundant of troops in which were/are expected to be able to fulfill the purpose of war of many countries. Due to the lacks of states in accommodating the amount of their national armies, therefore there is an expansion of private sectors as contractor of military and security services which nowadays are globally known as Private Military and Security Companies (PMSC) The research of the paper mainly uses the method of Normative Legal Writing Approach (Normative Judiciary) with Qualitative Data Approach. The method of Normative Judiciary is used within this research is harnessed to explore on the legal norms in the constitution regarding Private Military Contractors or companies which provide the private military services in order to be perceived upon the International Laws. The involvement of Private Military Contractors (PMC) in peacekeeping and security had been commenced from the Peace Operation in Africa, 1992, and begun to be seen from the 90s up to now. Contextually, due to the chaotic understanding upon the role, status, accountability, the regulation of the private military firms, and the international practice of PMC, therefore the role of UN Security Council (UNSC) and its authority in the sphere of national military activities of nations within international military conflicts is profoundly necessary. Based on the perspectives aforementioned, the research is able to formulate some of main problems incurred such as on how is the regulation of PMC in International Laws, on the use of PMC which is commonly globally practiced by the states, and on the role of UN Security Council (UNSC) in regards to authorize the states to use the PMC services within Enforcement Missions. In the end, we are able to summarize that the authorization of the use of Private Military Contractors (PMC) by UN Security Council is conductible upon nations based on the International Laws in general. Keywords: Private Military Contractors (PMC), Authorization 1The Student of Law Faculty of Universitas Sumatera Utara 2The Supervisor I, The Professor in Law Faculty of Universitas Sumatera Utara 3The Supervisor II, The General Academic Lecturer in Law Faculty of Universitas Sumatera Utara